Leukocyte's Hif-1 expression and training-induced erythropoietic response in swimmers - Mounier, R.; Pialoux, V.; Cayre, A.; Schmitt, L.; Richalet, J. P.; Robach, P.; Lasne, F.; Roels, B.; Millet, G.; Coudert, J.; Clottes, E.; Fellmann, N. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Altitude training is popular among athletes to augment oxygen delivery capabilities to tissues and to improve physical performance. Hypoxia inducible factor-1 (HIF-1) controls the expression of several genes' encoding involved in physiological responses towards reduced oxygen availability, in particular by increasing serum erythropoietin (EPO). It may be involved in the individual variability for erythropoietic markers and/or sea-level performance of athletes using altitude during their training. Therefore, we investigated whether, before training, evolutions of hif-1[alpha] and ahif (HIF-1[alpha] natural antisense) transcript amounts and HIF-1[alpha] protein quantities in leukocytes measured during an acute hypoxia normobaric test (3 h at 3000 m at rest) could allow to predict poor and good responders for hematological markers after a "living high-training low" protocol.